A tradução do insólito político latino-americano na narrativa de ficção de Ezequiel Martínez Estrada - Santos, Sérgio Wladimir Cazé dos (2021)
This dissertation analyses the novel Conspiración en el país de Tata Batata, by Argentine writer Ezequiel Martínez Estrada, an unfinished work edited posthumously in 2014 (fifty years after his death) in a volume edited by Ariel Magnus, also a writer, who tried to give a coherent composition to the 80 unpublished fragments left by the author. It compares the novel with four of his short stories, in which issues of social organization and political and state power are discussed explicitly: “La inundación” (1943), “Sábado de Gloria” (1944), “Examen sin consciencia” (1949) and “No me olvides” (1957). The dissertation analyses how Martínez Estrada translates in the novel ideas and positions that he had developed previously in his short stories and essays interpreting the Argentine and Latin American realities, underscoring his concerns with political instability and authoritarian power in his country and the continent. In Conspiración en el país de Tata Batata, this concern is reflected in formal terms in the work’s very own fragmentation and unfinishedness, which aesthetically reconfigure the experience of cyclical occurrence of institutional ruptures and installation of bureaucratic-authoritarian regimes in Central and South Americas, and in the Caribbean. By pointing out how the Latin American political uncanny is translated in Conspiración en el país de Tata Batata, this dissertation argues it is possible to identify in the fictional work, which transposes fundamentally Argentine issues to those connected with the overall Latin American reality, a narrative strategy based on uncanny, where the narrator builds in the novel an imaginary country that allows him to avoid, whenever suitable, any direct allusion to any actual country. In developing this approach, I survey existing literary criticism of Martínez Estrada’s fictional narratives, especially those delving into the short stories that make up the corpus, and the concept of ominous real (Liliana Weinberg); employ historical contextualization following a social-critical approach guided by the considerations of Antonio Candido; discuss Martínez Estrada’s ideas on fantastic literature in Hudson, Balzac and Kafka; and appropriate theorizations on the marvelous realism (Chiampi) and historical discourse (Barthes), to conduct literary criticism on a work that intersects two temporalities, the one of its writing and its posthumous reception.